New Bound and Hybrid Composite Insulation Materials from Waste Wheat Straw Fibers and Discarded Tea Bags - Mohamed Ali; Redhwan Almuzaiqer; Hassan Alshehri; Mohammed A. Alanazi; Turki Almudhhi; Abdullah Nuhait (Buildings, 2025)
This study utilizes waste wheat straw fibers and discarded tea bags as novel raw materials for developing new thermal insulation and sound absorption composites. Wood adhesive (WA) is used to bind the polymer raw materials. Loose polymers and different composites are experimentally developed in different concentrations. Sound absorption and thermal conductivity coefficients are obtained for the developed boards. Bending moment analysis and the moisture content of the boards are reported in addition to a microstructure analysis of the straw fibers from wheat. The results indicate that as the wheat straw fiber’s percentage increases in the composite, the thermal conductivity coefficient decreases, the flexure modulus decreases, the sound absorption coefficient increases at some frequencies, and the moisture content increases. The range of thermal conductivity and the noise reduction coefficient are 0.042–0.073 W/m K and 0.35–0.6 at 24 °C for the polymer raw materials, respectively. The corresponding values for the composites are 0.054 and 0.0575 W/m K and 0.45–0.5, respectively. The maximum moisture content percentages for the polymers and composites are 6.5 and 1.15, respectively. The composite flexure modulus reaches maximum and minimum values of 4.59 MPa and 2.22 MPa, respectively. These promising results promote these polymer and composite sample boards as more convenient insulation materials for green buildings and could replace the conventional petrochemical thermal insulation ones.